Political economy of development in India - "Bardhan ,Pranab" (Delhi, 2014)
In this readily accessible book Bardhan examines the political and social constraints on Indian development. In the newly added epilogue Bardhan comments on the process of liberalization in the 1990 s and examines the feasibility of the exercise in the light of ground realities. This ambitious and controversial book is essential reading for students of economics, politics and the general interested reader.
Keywords: Economic history-India:Economic policy-India:Economics